MN=6cm
NP= 4 cm
Explanation:
Step 1:
By the property of symmetry in triangle
![(BA)/(BC) =(MN)/(NP)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6izg151lb8i4enj8nrx3mkmact4lby0fi4.png)
By applying componendo and dividendo rule above equation is modified as
![(BA+BC)/(BA-BC) = (MN+NP)/(MN-NP)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ybwcptpxh6fhidwsrjhchwk8tgp6g7bcdv.png)
Step 2:
Applying the values in above equation
![(12+8)/(12-8) =(10)/(MN-NP)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8eseh26rwws0mk0qd7rnil60sf0qcdqao6.png)
on simplification
MN-NP=
![(10*4)/(20)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iwgnrm98hxwxrspjvv1lwdhfoplcm5x9z2.png)
MN-NP=2
MN+NP=10
on solving above equations
2
MN=12
MN=6 cm
NP=10-MN
=10-6
=4 cm